Critical Discourse Analysis on Portraying the CODE-PLAN Model to Create Lesson Plan - Azizah, Shofiah Nur (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This library research critically examined the specific cognitive skills teachers need to create effective lesson plans using the CODE-PLAN model. The study explored how the dimensions of content, social context, and time interact to influence lesson planning and identified six key strands such as content transformation, task creation, adaptation to learning disposition, clarity of learning objectives, unit contextualization, and phasing. The researcher used a qualitative descriptive-analytical method and content analysis to analyze the data. The study aimed to highlight the cognitive demands essential for effective lesson planning. The findings suggest that applying the CODE-PLAN model could enhance teachers’ instructional practices, thereby improving educational quality and student learning outcomes. However, challenges in teacher training and resource limitations need to be addressed for successful implementation. Moreover, the research contributes to the field by providing a framework for understanding and improving the cognitive demands in lesson planning, potentially guiding curriculum design and teacher training programs. Keywords: CODE-PLAN Model, Cognitive Skills, Lesson Plan